Ξ-nuclear constraints from 𝚵− emulsion capture events - Friedman Eliahu; Gal Avraham (EPJ Web of Conferences, 2022)
All five KEK and J-PARC two-body Ξ−+AZ → A′ΛZ’ + A″ΛZ” capture events in light emulsion nuclei, including KISO and IBUKI in 14N, are consistent with Coulombassisted 1pΞ− nuclear states. The underlying Ξ-nuclear potential is strongly attractive, with nuclear-matter depth VΞ larger than 20 MeV. The recent 14N capture events KINKA and IRRAWADDY assigned by J-PARC E07 to 1sΞ− nuclear states, and implying considerably shallower VΞ, have also another interpretation as 1pΞ0 nuclear states.